Experiência de trabalho temporário de psicólogos que atuaram no CREAS - Pauli, Cassiele Gomes (2017)
Psychology has been increasingly active in the field of Social Assistance, absorbing a significant number of professionals currently. It is important to note that hirings are carried out by municipal governments, which direct professionals to Social Assistance services, one of them is the Reference Center for Specialized Social Assistance (CREAS). Thus, this dissertation aims to identify the meaning of the work for temporary psychologists who worked in the field of Social Assistance, specifically CREAS, in an interior municipality of the Rio Grande do Sul. Based on the theoretical assumptions in Psychodynamics of Work, by Dejours, it is a qualitative research of transversal and exploratory nature, with descriptive nature. Six psychologists participated in this study who worked on a CREAS, under a temporary work contract, between the years 2010 to 2015. For this purpose, a procedure called snowball was used to recruit psychologists. Participants answered a semi-structured individual interview, which was analyzed through Content Analysis. This analysis gave rise to four categories: The field of Social Assistance as an opportunity to work for Psychology, The experience of work in CREAS and the reflexes in Career Planning, Precarization of temporary work in CREAS and, finally, The meaning that the CREAS temporary psychologists gave to this work experience. From the results of such categories, it was possible to perceive that the temporary work for the psychologists interviewed was great value, and for many of them it was the first job as psychologists, which promoted a sense of recognition and identification with problems faced. On the other hand, it was an experience of much investment, wear, frustration and illness.